2022
DOI: 10.1111/ejss.13317
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dicranopteris linearis roots on the shear strength of different soil layers in collapsing wall of Benggang

Abstract: ‘Benggang’ is a local term for a widespread type of severgully erosion with steep collapsing walls in granitic, low, hilly areas of southern China, and its development and expansion are closely related to the shear strength of the collapsing wall. Plant roots play an important role in improving soil shear strength. However, the shear strength of root‐soil complexes in different layers of collapsing walls remains obscure. We selected Dicranopteris linearis fern roots and adopted the direct shear method to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…Shuai et al [22] suggested that among the four herbs plants, the soil reinforcement effect of Pennisetum sinese and Odontosoria chinensis was higher than that of Dicranopteris linearis and Neyraudia reynaudiana. In the three layers of collapsing wall, the root system of Dicranopteris linearis significantly increased the shear resistance and compressive strength of the first layer but not in the other two [19,23]. In short, root density [19,24], species of plants [25] and soil properties and configurations [26] affect the effect of the root system on soil reinforcement.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Shuai et al [22] suggested that among the four herbs plants, the soil reinforcement effect of Pennisetum sinese and Odontosoria chinensis was higher than that of Dicranopteris linearis and Neyraudia reynaudiana. In the three layers of collapsing wall, the root system of Dicranopteris linearis significantly increased the shear resistance and compressive strength of the first layer but not in the other two [19,23]. In short, root density [19,24], species of plants [25] and soil properties and configurations [26] affect the effect of the root system on soil reinforcement.…”
Section: Introductionmentioning
confidence: 88%
“…In the three layers of collapsing wall, the root system of Dicranopteris linearis significantly increased the shear resistance and compressive strength of the first layer but not in the other two [19,23]. In short, root density [19,24], species of plants [25] and soil properties and configurations [26] affect the effect of the root system on soil reinforcement.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In recent years, scholars have conducted several studies on the soil consolidation effect of plant roots. Indoor or field tests have confirmed the ability of plant roots in significantly improving the shear strength and ductility of soil [1][2][3][4][5][6][7][8][9] . These research results have shown that the natural attributes of roots considerably affected the soil consolidation effect, such as their species [10][11][12][13][14][15] , growth age [16][17][18][19] , and root morphology [20][21][22][23][24] .…”
mentioning
confidence: 99%
“…Plant root-soil complexes are important features influencing soil characteristics such as soil structural stability and functions. Zhou et al (2022), employing a Dicranopteris linearis fern root-soil system and an adopted direct shear measurement methodology, illustrated that roots could improve the collapsing-wall soil shear strength typically in soil lateritic layer other than the sandy and detritus layers. They further established new shear strength equations for root-soil complexes of D. linearis based on the modified Wu-Waldron model and Coulomb's formula.…”
mentioning
confidence: 99%